2004
DOI: 10.2323/jgam.50.243
|View full text |Cite
|
Sign up to set email alerts
|

Comamonas badia sp. nov., a floe-forming bacterium isolated from activated sludge

Abstract: IntroductionBacteria in activated sludge usually aggregate with each other and this process is called floc formation. This floc formation is an integral part of the activated sludge process. In a previous paper (Tago and Aida, 1977), we reported on a floc-forming bacterium isolated from activated sludge and mentioned that it belongs to the genus Pseudomonas, although it is not classifiable into one of the described species. Here, we describe morphological, phenotypic, phylogenetic and genomic characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…The fatty acid pattern of the strain YY287 T is shown in Table 1 in comparison with other representative Comamonas species. The fatty acid profile of strain YY287 T was in good agreement with data obtained for other members of the genus Comamonas (Chang et al, 2002;Wauters et al, 2003;Tago &Yokota, 2004;Chou et al, 2007) (Table 1).…”
supporting
confidence: 76%
See 2 more Smart Citations
“…The fatty acid pattern of the strain YY287 T is shown in Table 1 in comparison with other representative Comamonas species. The fatty acid profile of strain YY287 T was in good agreement with data obtained for other members of the genus Comamonas (Chang et al, 2002;Wauters et al, 2003;Tago &Yokota, 2004;Chou et al, 2007) (Table 1).…”
supporting
confidence: 76%
“…nov.); 2, C. odontotermitis Dant3-8 T ; 3, C. koreensis DSM 18232 T ; 4, C. testosteroni DSM 50244 T ; 5, C. terrigena LMG 1253 T ; 6, C. denitrificans DSM 17887 T ; 7, C. nitrativorans DSM 13191 T ; 8, C. aquatica LMG 2370 T ; 9 C. kerstersii LMG 3475 T ; 10, C. badia DSM 17552 T . The data for species C. koreensis, C. testosteroni, C. terrigena, and C. badia were obtained from Chang et al (2002) and Tago & Yokota (2004). The data for C. odontotermitis, C. denitrificans, C. nitrativorans, C. aquatica and C. kerstersii were obtained from Chou et al (2007).…”
Section: Description Of Comamonas Composti Sp Novmentioning
confidence: 99%
See 1 more Smart Citation
“…Ma et al (2015a) and Zhu et al (2016) also observed a higher abundance of Thiobacillus and Comamonas in aerobic activated sludge treating CWW. Additionally, certain species of detected bacteria, such as Comamonas and Ottowia, are floc-forming bacteria (Tago and Yokota 2004;Felföldi et al 2010) and might play significant roles in active sludge structure formation, and hence contribute to the stability of the aerobic system.…”
Section: Discussionmentioning
confidence: 99%
“…Diphosphatidylglycerol (DPG), phosphatidylglycerol (PG) and phosphatidylethanolamine are the major polar lipids of species of the genus Comamonas (Zhu et al, 2014;Sun et al, 2013). Type strains of species of this genus have been collected from different environmental samples like activated sludge (Tago & Yokota, 2004;Chipirom et al, 2012;Gumaelius et al, 2001), compost (Zhu et al, 2014;Young et al, 2008), waste water treatment granules (Kim et al, 2008), wetlands (Chang et al, 2002), agricultural soils (Chitpirom et al, 2012), forest sediments , termite gut (Chou et al, 2007), landfill leachate (Etchebehere et al, 2001), sludge and soil (Sun et al, 2013) and phenol-contaminated soil (Yu et al, 2011). At the time of manuscript writing a total of 18 species names are validated in this genus while 'Comamonas faecalis' (Kim & Lee, 2014) does not yet have validly published name.…”
mentioning
confidence: 99%